RESPONSIBILITY IN SUSTAINABILITY PRINCIPLES IMPLEMENTATION IN INTERNATIONAL OIL TRADE - Puteri, Dina Silvia (Journal of Private and Commercial Law, 2024)
As globalization grows, it eliminates national boundaries and accelerates international trade, with petroleum being the most traded commodity. However, petroleum, a fossil fuel, produces carbon emissions that contribute to global warming. In response, the principle of sustainability emerged, focusing on ensuring that today's activities do not harm future generations. This study explores the responsibility of upholding sustainability in international oil trade. Specifically, it examines how the principle is adopted in global oil trade and how Indonesia implements it. The research uses a normative-critical approach, including statutory, conceptual, and legal analyses. To align with sustainability, international oil companies must address environmental, social, and economic impacts through the triple bottom line framework, namely people, planet, and profit. By incorporating these principles into their annual reports, oil companies can demonstrate their commitment to sustainability.